Effects of copy center particles on the lungs: a toxicological characterization using a Balb/c mouse model. (25th July 2013) - Pirela, Sandra; Molina, Ramon; Watson, Christa; Cohen, Joel M.; Bello, Dhimiter; Demokritou, Philip; Brain, Joseph
Abstract: Context : Printers and photocopiers release respirable particles into the air. Engineered nanomaterials (ENMs) have been recently incorporated into toner formulations but their potential toxicological effects have not been well studied. Objective : To evaluate the biological responses to copier-emitted particles in the lungs using a mouse model. Methods : Particulate matter (PM) from a university copy center was sampled and fractionated into three distinct sizes, two of which (PM0.1 and PM0.1–2.5 ) were evaluated in this study. The particles were extracted and dispersed in deionized water and RPMI/10% FBS. Hydrodynamic diameter and zeta potential were evaluated by dynamic light scattering. The toxicological potential of these particles was studied using 8-week-old male Balb/c mice. Mice were intratracheally instilled with 0.2, 0.6, 2.0 mg/kg bw of either the PM0.1 and PM0.1–2.5 size fractions. Fe2 O3 and welding fumes were used as comparative materials, while RPMI/10% FBS was used as the vehicle control. Bronchoalveolar lavage (BAL) was performed 24 hours post-instillation. The BAL fluid was analyzed for total and differential cell counts, and biochemical markers of injury and inflammation. Results : Particle size- and dose-dependent pulmonary effects were found. Specifically, mice instilled with PM0.1 (2.0 mg/kg bw) had significant increases in neutrophil number, lactate dehydrogenase and albumin compared to vehicle control. Likewise, pro-inflammatory cytokines were elevated in mice exposed to PM0.1 (2.0 mg/kg bw) compared to other groups. Conclusion : Our results indicate that exposure to copier-emitted nanoparticles may induce lung injury and inflammation. Further exposure assessment and toxicological investigations are necessary to address this emerging environmental health pollutant.